Menggali Makna Siraman Pengantian Budaya Jawa sebagai Simbol Kesucian dan Berkat dalam Perkawinan Katolik - F. Christa Natalia; Intansakti Pius X (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the symbolic meaning of the siraman ceremony in Javanese culture and interpret its values ​​in light of the Catholic faith, particularly regarding the sanctity and blessings of the sacrament of marriage. The siraman tradition is understood not merely as a cultural ritual, but as a process of physical and spiritual purification imbued with spiritual symbolism, such as the use of water from seven springs and the granting of parental blessings. This study uses a qualitative approach with a literature review method through analysis of Church documents, Javanese anthropological literature, and relevant research. The results indicate that the meaning of purification in siraman is closely related to the symbolism of baptismal water in the Catholic tradition, while the prayer of parental blessing aligns with the concept of blessing as a manifestation of God's grace in the family. Through the inculturation perspective emphasized in Gaudium et Spes and Ecclesia in Asia, siraman can be understood as a form of harmonious dialogue between faith and culture without compromising the purity of Church teachings. This study concludes that the siraman ceremony can enrich the experience of the sacrament of marriage for Javanese Catholics, while strengthening their identity as individuals of faith and culture.